The use of African languages in schools : the case of South Africa - (:unkn) unknown (My University, 2017)
The principal goal of this research study is to is to investigate the use of African languages in the post-apartheid South African education system. Based on fieldwork, the study analyses, for main support data, five primary schools and two high schools of the Pretoria city townships, and for control data, two primary schools, one in Johannesburg, the other a Pretoria inner city model-C school. The data collected accurately represent the variety of existing situations. Having reviewed the history of previous language policies and practices, the author explores current practices in classrooms and their conformity with the 1997 recommendation that languages of learning and teaching should be languages of the learners for four years to be replaced by English there after. The study highlights the fact that the prevalent use of Pretoria-Sotho, a predominant urban variety that has become a mother tongue for the great majority of the inhabitants of these townships, is detrimental to standardised forms of the African languages. It concludes that this practice is due to a lack of competence in African languages, by both teachers and learners alike. The outcome is in contradiction with the official recommendation and heavily influences the transmission of standardised forms of the African languages leading to high and disastrous failure rates in these schools. Thus, the study strongly advocates for a bi-multilingual education based on the mother tongue and brings to the surface the need for the adoption of a more contextualized pedagogical concept such as translanguaging which introduces second/foreign language teaching methodologies, to palliate the language gap between the language practices in these schools and the policy recommendation. Following this policy recommendation, translanguaging offers the possibility to promote, transmit and improve proficiency in both the standardised forms of the African languages as well as in English. Finally, translanguaging
Keywords: African Research